Violence Against Ahmadiyya as Productive Intolerance: Adressing Jeremy Menchik’s Godly Nationalism - Rizkita, Muhammad; Riyanto, Waryani Fajar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article examines godly nationalism using the theory of secularism. This connection is based on a shared